Obstructive Sleep Apnea Patients Having Surgery Are Less Associated with Glaucoma - Hsin-Yi Chen; Yue-Cune Chang; Che-Chen Lin; Fung-Chang Sung; Wen-Chi Chen (Journal of Ophthalmology)
Objective. To investigate if different treatment strategy of obstructive sleep apnea (OSA) was associated glaucoma risk in Taiwanese population. Methods. Population-based retrospective cohort study was conducted using data sourced from the Longitudinal Health Insurance Database 2000. We included 2528 OSA patients and randomly selected and matched 10112 subjects without OSA as the control cohort. The risk of glaucoma in OSA patients was investigated based on the managements of OSA (without treatment, with surgery, with continuous positive airway pressure (CPAP) treatment, and with multiple modalities). The multivariable Cox regression was used to estimate hazard ratio (HR) after adjusting for sex, age, hypertension, diabetes, hyperlipidemia, and coronary artery disease. Results. The adjusted HR of glaucoma for OSA patients was 1.88 (95% CI: 1.46–2.42), compared with controls. For patients without treatment, the adjusted HR was 2.15 (95% CI: 1.60–2.88). For patients with treatments, the adjusted HRs of glaucoma were not significantly different from controls, except for those with CPAP (adjusted HR = 1.65, 95% CI = 1.09–2.49). Conclusions. OSA is associated with an increased risk of glaucoma. However, surgery reduces slightly the glaucoma hazard for OSA patients.